Personality Traits and Household Consumption Choices - Lucia Mangiavacchi; Luca Piccoli; Chiara Rapallini (Institute of Labor Economics (IZA), 2018)
In this paper, we test whether consumption choices are affected by personality traits and whether this impact is different for singles and individuals living in couples. To fulfill this aim, we test the impact of personality on preferences for different commodities using the German Socio-Economic Panel (SOEP) and estimating a system of Engel curves that includes personality traits as demographic shifters. The analysis is conducted on four different samples: single men, single women, childless couples and couples with children. The inclusion of personality traits among demographic shifters helps to reduce unobserved heterogeneity and improves the goodness of fit of the Engel curves specification by an average of 15.7%. In comparing the results for singles and couples, we find evidence of a consumption-based marital surplus for Mental Openness and Conscientiousness. These traits are characterized by positive assortative mating, and they have a significant and consistent impact on the expenditure for several commodities for both singles and couples. For instance, similarly open-minded partners are likely to spend household resources on culture, and their joint consumption of such goods may be a potential reason for their marital surplus.
Keywords: D12; J16; I31; 330; consumption choices; preferences; Big Five personality traits; martial surplus; assortative mating